FORAMINIFERAL RECORD OF ENVIRONMENTAL CHANGES: PREEVAPORITIC DIATOMACEOUS SEDIMENTS FROM GAVDOS ISLAND, SOUTHERN GREECE. - Drinia, H.; Antonarakou Α.; Tsaparas, N.; Dermitzakis, M. D.; Kontakiotis, G. (Bulletin of the Geological Society of Greece, 2018)
The Messinian pre-evaporitic sedimentary succession of Gavdos island (Metochia section) is a nearly uninterrupted succession of marine sediments, dominated by finely laminated diatomaceous sediments, which are cyclically alternating with marlstone and white limestone beds. The purpose of this study is to analyze in detail the benthic and planktonic foraminiferal microfauna preserved in the sediments of this section. The qualitative and quantitative analysis of the planktonic foraminifera fauna allowed the recognition of seven bioevents, which have been astronomically dated for the Mediterranean. The base of the diatomitic succession in Gavdos Island is dated at 6.696 Myr, whereas its top at 6.0 Myr. Our results suggest that two environmental parameters are the most important factors that control the community structure of the benthic foraminiferal fauna: the food availability and oxygen concentration. In addition, local upwelling phenomena evidenced by signals from the benthic foraminifera and the distribution pattern of the planktonic G. bulloides may have played a role in the faunal density and composition